Os Beatos - Miguélez Cavero, Alicia (2018)
Este artigo tem com objetivo principal apresentar um conjunto de manuscritos, comummente conhecidos com o nome de Beatos, que são cópias dum Comentário ao Apocalipse atribuído ao monge Beato de Liébana, que o teria escrito no norte da Península Ibérica no século oitavo. Deste Comentário conservam-se hoje em Portugal duas testemunhas, uma delas copiada e iluminada no Mosteiro de São Mamede de Lorvão em 1189. The main aim of this article is to present a set of manuscripts commonly known by the name of “Beatus”, which are copies of a Commentary on the Apocalypse attributed to the monk Beatus of Liebana, who would have written in the north of the Iberian Peninsula in the eighth century. Two witnesses of this work are preserved today in Portugal, one of them copied and illuminated in the Monastery of São Mamede de Lorvão in 1189.